The Challenges of Learning Loss in English Language Learning at Islamic Higher Education in the Post Pandemic - Susanto Susanto (Script Journal: Journal of Linguistics and English Teaching, 2022)
Background: The occurrence of the Covid-19 pandemic forced educational institutions to change learning methods and techniques, especially at Islamic universities in Indonesia. Learning loss is a separate obstacle that must be faced after the COVID-19 pandemic. This study aims to describe lecturers' factors, strategies, and roles in dealing with learning loss in learning English at Islamic universities in Indonesia. Methodology: This study examines or interprets written materials based on the context of published records, textbooks, newspapers, periodicals, and articles. This paper's method guided the writing of research-based conclusions. These conclusions defined "learning loss" and examined the English learning problems at Islamic universities in Indonesia following the pandemic. Descriptive-qualitative methods get facts and interpretations. This method studies deductive and inductive reasoning up to the level of description. Findings: This study finds some factors of learning loss in English learning at Islamic universities, such as internet access, the quality of their distance education program, families, and engagement. Conclusion: This research concludes that in overcoming learning loss after the COVID-19 pandemic, learning recovery is carried out by all parties, including the university, lecturers, the entire campus academic community, and local and central governments, by designing the Independent Learning Curriculum. Originality: This research demonstrates that the COVID-19 pandemic significantly impacts English learning. In addition, this study identifies the causes of student learning loss at Islamic universities.